Transístor BJT: uma visita interactiva pelo passado, presente e futuro - Cabrita, Isabel (2012)
This paper focuses on the description of a hypermedia prototype, which admits various links to the Internet, mainly planned for pupils of the 10th year in courses of Electronics in a secondary level. In these courses, the discipline Electronics focuses on the subject BJT transistor. Considerations regarding the way the document should be explored are also made, considering the established objectives: To contribute for the pupils to i) become aware and motivated regarding issues related to the historical context of the subject; ii) broaden their knowledge about the way the transistor operates; iii) become acquainted with some of its main applications; iv) reflect critically about the future within this subject; v) develop navigation capacities in hypermedia products, namely in specific sites; vi) develop their taste for a permanent and autonomous type of learning; vii) develop capacities of persistence and viii) become sensitive towards the technological and scientific development.